Analisis Penerapan ISO 9001: 2015 pada PT KAI: Sebuah Tinjauan Literatur Naratif - Rahmawati, Aprilia; Rosdiana, Dina; Asbari, Masduki; Sutardi, Didi; Sukriyah, Sukriyah; Fauji, Ahmad; Gazali, Gazali; Novitasari, Dewiana (JUBISMA, 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the analysis of the implementation of ISO 9001: 2015 at PT. Kerta Api Indonesia (PERSERO) to identify and summarize previously published articles without any criticism for the articles being reviewed. The review results show that PT. Kereta Api Indonesia describes the management of railroad asset documents based on ISO 9001: 2015 concerning Quality Assurance Systems in supporting the revitalization program of several railroads in Indonesia. In the process of revitalizing the rail line, of course, documents are needed as the main reference. Asset documents used in the railroad track revitalization activities are documents in the form of technical drawings, asset ownership documents, and cartography. The data used in this research is primary data, obtained from participatory observation in 2019, in-depth interviews, and a review of document asset document management activities. Along with the development of increasingly advanced industry, companies are also required to provide the best quality in the products and services they produce but do not forget the environmental impacts that occur from all company activities. In the era of globalization, the challenge for an institution, both government and private, is the ability to guarantee customer or work partner satisfaction. Likewise with the State-Owned Enterprises (BUMN) PT. Kereta Api (Persero). The conclusion obtained is that asset document management on the basis of ISO 9001: 2015 has an important role in supporting the railroad revitalization program in Indonesia. This is because in revitalizing the railroad, guidelines are needed to reconstruct the structure of the railroad when the track was still actively used. If the asset documents are damaged, both physically and in terms of information, then the reconstruction process will require more money and take longer.